Validation of H2O2-mediated pathway model for elucidating oxygen reduction mechanism: Experimental evidences and theoretical simulations. (1st August 2019) - Yin, Fengjun; Liu, Yuan; Wang, Sha; Wang, Chuan; Liu, Hong
Abstract: Oxygen reduction reaction (ORR) on an electrode is a multi-step process that involves both H2 O and H2 O2 as final products, and the mechanism focusing on the productions of them has yet to be elucidated. In this study, simplifying the multi-step process of ORR by means of rate-limiting step (RLS) led to a H2 O2 -mediated pathway model. This model accounts for the productions of H2 O and H2 O2 by the H2 O2 -mediated strategy existing in 2 × 2e pathway. The model links the overall reaction with RLS and serves to establish the electrochemical kinetic equations of sub-processes. A tending degree (RH2O2 ) quantifying the "tendency" toward H2 O and H2 O2 was proposed. Finally, a mathematic approach based on the H2 O2 -mediated strategy are formed and well account for two common ORR behaviors: i) H2 O2 is inevitably produced on most of the ORR catalysts, including Pt-based catalysts, and ii) the tendency is regulable from external factors rather than merely determined by the intrinsic properties of catalysts. Furthermore, this model is fully validated by the kinetic simulations of the ORR behaviors in the rotating ring-disk electrode (RRDE) system. This study opens a way to advance the ORR applications by regulating the tendency, and may facilitate the comprehensive understanding of ORR mechanism.